Anal Intraepithelial Neoplasia from a Pathologists Point of View - Lyons, Keegan M.; Butler, Samantha L. (Clinics in Colon and Rectal Surgery, 2018)
Anal squamous cell carcinoma is a relatively rare diagnosis, but its incidence has continued to rise. Anal squamous cell carcinoma and its precursor lesion, anal intraepithelial neoplasia (AIN), are human papillomavirus (HPV)-associated squamous neoplasias. High-risk HPV subtypes cause cellular proliferation in the anal transformation zone mucosa leading to similar dysplastic changes as seen in the cervix. Unified cytologic and histologic classification systems have emerged for all HPV-associated squamous lesions of the lower anogenital tract due to recent advancements in the understanding of these lesions. P16 immunohistochemical stain, a biomarker for HPV, is recommended in the diagnosis of HPV-associated lesions. The unity of terminology will aid in communication between pathologists and clinicians, ultimately leading to improved patient care.
Keywords: anal intraepithelial neoplasia; human papillomavirus; lower anogenital squamous terminology; LAST standardization project